Psychological Impact of Exposure to the COVID-19 Sanitary Crisis on French Healthcare Workers: Risk Factors and Coping Strategies - Vancappel, Alexis; Jansen, Eline; Ouhmad, Nawal; Desmidt, Thomas; Etain, Bruno; Bergey, Chantal; d'Ussel, Marguerite; Krebs, Marie-Odile; Paquet, Claire; Réveillère, Christian; Hingray, Coraline; El-Hage, Wissam (Frontiers in Psychiatry, 2021)
Abstract Background: COVID-19 sanitary crisis is associated with emotional difficulties such as depression, anxiety and reactional post-traumatic symptoms among healthcare workers. Indeed, healthcare workers were particularly exposed to COVID-19 sanitary crisis. This study aimed to investigate the effects of exposure to COVID-19 sanitary crisis on affective symptoms (anxiety, post-traumatic stress, burnout) among French healthcare workers and the mediating role of cognitive emotion regulation strategies (positive re-evaluation and set in perspective) and coping strategies (active coping, planning, instrumental support, emotional support, emotional expression, positive reappraisal, acceptance, denial, blame, humor, religion, distraction, substance use, behavioral disengagement). Method: This cross-sectional survey-based study collected demographic data and mental health measurements from 1,010 volunteers (838 women) who consented online to participate, from March 24 to June 28, 2020, in France. Participants filled out online questionnaires and visual analogic scales that evaluate affective symptoms related to the COVID-19 sanitary crisis, namely symptoms of post-traumatic stress, burnout, emotion regulation abilities, and coping abilities. Results: The majority (57.8%) of the participants presented post-traumatic symptoms. Depending on the sub-dimensions evaluated, a proportion of participants reported moderate (25.9%-31.2%) to severe (17.2%-40.7%) burnout symptoms. We found a significant effect of the level of exposure to COVID-19 on affective symptoms. Being a woman, having a lower job position and having less experience were associated with higher level of affective symptoms. Moreover, coping strategies had a mediating effect on the relation between stress and burnout, supporting the coping reserve model. Conclusion: Post-traumatic and burnout symptoms were highly prevalent among French healthcare workers at the beginning of the COVID-19 crisis. Exposure to COVID-19 is a determining factor. We can thus promote both coping training and a good environment to limit the emotional consequences of exposure to COVID-19.